The role and outcomes of music therapy during pregnancy: a systematic review of randomized controlled trials - Chao Ji; Jing Zhao; Qiaole Nie; Shuo Wang (Taylor & Francis Group, 2024)
AbstractIntroduction The abundant functions of music and its effects on human's mental and physical health have been verified since ancient times, but rarely received attention as an alternative obstetric intervention.Objective This study aims to investigate the benefits of music therapy on prenatal and delivery experiences of pregnant women.Method A systematic search for articles was conducted in electronic databases including CINAHL, Web of Science, PubMed/Medline, and CNKI. A total of 240 articles were identified, and 17 studies were selected for this review. The extracted data included author, year, location, sample size, intervention phase, type of music, music therapy strategy, measuring instruments, and results. The data were organized chronologically based on the publication year of each study.Result The articles indicated that music therapy has advantages in reducing pain during childbirth, lowering anxiety and stress levels in mothers, improving sleep quality, and increasing fetal movements, basal fetal heart rate, and accelerations.Conclusion Based on the findings, it can be concluded that music therapy is an effective approach to enhance the experience of pregnant women during pregnancy and delivery. Therefore, its implementation in obstetrical clinical practice is highly recommended.